(untitled) (International Journal of Innovative Research in Engineering & Management, 2022)
Soil stabilisation is the process of modifying soils in order to improve their physical qualities. Stabilization can improve a soil’s load bearing capacity to support pavements and foundations by increasing its shear strength and controlling its characteristics. Stabilization can be used to remediate a variety of soil types, including expansive clays and granular materials. A wide range of additives, such as silica, lime, plant roots, fly-ash, and cement, are used in this process. This project deals with studying the stabilization of soils using plant roots and lime. Samples were collected in this experiment from the Heerpora area of Shopian (J&K) in the year 2021 with the aim to quantify the effect of plant roots and lime on unconfined compressive strength, california bearing ratio. The physical and engineering qualities of the soil were determined through experimental examinations. The material accessible at this area was fine-grained dirt that was silty and clayey in nature. The treatments consisted of five samples with lime and plant roots (0%, 1.5% 3%, 5.0%, 7.0%). The unconfined compressive strength showed an increase with the addition then decrease the study found that optimum percentage of lime and plant root is 3% of dry soil.